2020
DOI: 10.1186/s12904-020-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Who needs and continues to need paediatric palliative care? An evaluation of utility and feasibility of the Paediatric Palliative Screening scale (PaPaS)

Abstract: Background: While the populations of children who can benefit from paediatric palliative care (PPC) have been broadly defined, identifying individual patients to receive PPC has been problematic in practice. The Paediatric Palliative Screening scale (PaPaS) is a multi-dimensional tool that assesses palliative care needs in children and families to facilitate timely referrals. This study evaluates its use to manage new referrals and ongoing review of patients receiving home-based PPC in Singapore. Methods: Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 33 publications
0
37
0
4
Order By: Relevance
“…In an earlier study that used this tool, Chong et al reported the utility and feasibility of the PaPaS as a tool for screening admissions or determining the continuation of PPC after 1 year of home-based PPC service. This study demonstrated the transparency and reliability of the PaPaS through its objective and standardized scoring system, and suggested that widespread adoption of the PaPaS may minimize the gaps in communication, continuity of care, and collaboration across settings [ 7 ]. However, both the original author of the PaPaS and Chong’s studies were based on the PaPaS assessed by PPC specialists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an earlier study that used this tool, Chong et al reported the utility and feasibility of the PaPaS as a tool for screening admissions or determining the continuation of PPC after 1 year of home-based PPC service. This study demonstrated the transparency and reliability of the PaPaS through its objective and standardized scoring system, and suggested that widespread adoption of the PaPaS may minimize the gaps in communication, continuity of care, and collaboration across settings [ 7 ]. However, both the original author of the PaPaS and Chong’s studies were based on the PaPaS assessed by PPC specialists.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the original author of the PaPaS and Chong’s studies were based on the PaPaS assessed by PPC specialists. The consistency of PaPaS assessment by primary care clinicians who are not familiar with PPC with the PPC team’s assessments has not been evaluated, considering that they may have considerably different perspectives and levels of understanding about PPC [ 7 , 13 , 14 ]. Therefore, we compared the palliative care needs assessed by primary clinical and PPC teams to evaluate the agreement between them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,[8][9][10] The most common strategy for early integration is through the adoption of one or more 'triggers', such as those in the Paediatric Palliative Screening Scale (PaPaS). 21 Many literature sources highlight the importance of improving access by providing paediatric palliative care in various settings, 22 and key policymaking organisations recommend this. 4,[8][9][10] This includes providing access to respite care, to ensure families have opportunities to manage the needs of their child with a life-limiting condition alongside the needs of other family members.…”
Section: Improving Accessmentioning
confidence: 99%